Octamolybdate metal organic complex as well as preparation method and application thereof
By the development of an octopus metal metal organic mathematical partner as a catalyst, the problem of low efficiency of traditional desulfurization technology in heavy fuel fuels is solved, and the efficient oxide desulfurization effect is achieved under mild conditions. sex.
Patent Information
- Application Number
- CN202411492962.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional hydrodesulfurization technology is inefficient in removing highly stable aromatic sulfides from heavy fuel oil, and the catalyst preparation method is complex, making it difficult to meet the demand for efficient desulfurization under mild conditions.
The development of an octopolytic metal organic mathematical partner Zn4 (MO8O26) (C12H8N5O2) 4. 24H2O as a non -exactly the catalytic performance through the hydrological reaction, and the catalytic performance was used during the oxidation desulfurization process.
This catalyst shows an excellent catalytic effect under mild conditions. It can achieve 99.9%of the oxidative desulfurization rate of 99.9%in 120 minutes, and has good circulation performance and stability, suitable for large -scale production.
Smart Images

Figure CN119371460A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel oil oxidation desulfurization, and particularly relates to an octamolybdate metal organic complex and a preparation method and application thereof. Background Art
[0002] With the rapid growth of the global economy and the acceleration of industrialization, the energy demand has surged, especially the massive consumption of fossil fuels, which has led to the intensification of a series of environmental problems such as sulfur oxides (SOx) and nitrogen oxides (NOx). As one of the key fossil energy sources, the pollutants released during the mining, processing and use of oil, especially SOx, have become the focus of global attention. SOx is not only the main cause of acid rain, but also causes atmospheric particulate pollution, posing a serious threat to human health and ecosystems. Therefore, strict control of sulfur content in petroleum products has become a key part of environmental protection policies in various countries.
[0003] Although traditional hydrodesulfurization (HDS) technology performs well in removing sulfides from light oil products, it is difficult to achieve ideal desulfurization effects for highly stable aromatic sulfides in heavy fuel oil because it needs to operate under high temperature and high pressure. In addition, the steric hindrance of these sulfides on the active sites of the catalyst also limits the efficiency of HDS. Therefore, the development of a new generation of desulfurization technology suitable for mild conditions has become a research hotspot.
[0004] In recent years, oxidative desulfurization (ODS) technology has been regarded as one of the most promising alternatives to traditional HDS technology due to its mild operating conditions, high selectivity, low cost and simple process flow. The core of ODS is to use catalysts with the help of oxidants to convert sulfides in oil products into a form that is easy to separate. The selectivity and activity of the catalyst directly affect the effect of ODS, so the development of efficient ODS catalysts is the key to current research.
[0005] Polymetallate (POM)-based metal organic complexes have shown potential as efficient and selective ODS catalysts due to their unique structure and properties. However, due to the diversification of coordination modes formed between different organic ligands and metal cations, the structure of POM-based organic complexes is rich and varied, which in turn affects its catalytic performance and limits the scope of application of such catalysts. For example, publication number CN103666536A discloses a method for oxidative desulfurization of FCC gasoline based on molybdenum polyoxometalates, but it is necessary to add ionic liquid as an extractant during its use to achieve separation of gasoline and liquid after desulfurization. If the extractant is not added, it is a homogeneous solution, and the subsequent separation steps are complicated. For another example, publication number CN116726993A discloses a preparation method of a zirconium-based molybdate oxidative desulfurization catalyst, although the catalytic performance of the catalyst is relatively excellent, the preparation method of its catalyst is relatively complicated. Therefore, it is crucial to design the structure of polymetallate (POM)-based metal organic complexes and develop a catalyst with a heterogeneous phase, a simple preparation method and high catalytic performance. Summary of the invention
[0006] In view of the above technical problems, the present invention provides an octamolybdate metal organic complex and a preparation method and application thereof.
[0007] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0008] An octamolybdate metal organic complex, the molecular formula of which is: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 organic ligand and twenty-four crystal water molecules; the unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0009] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps: dissolving zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate in distilled water, stirring at room temperature, and adjusting the pH value to acidic to obtain a suspension; subjecting the suspension to a hydrothermal reaction, and after the reaction is completed, naturally cooling to room temperature, washing, and drying to obtain regular colorless crystals, namely the octamolybdate metal organic complex.
[0010] The molar ratio of the zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate is (3.5-5.5):(1.2-2.5):1.
[0011] More preferably, the molar ratio of the zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate is (4.0-5.0):(1.5-2):1.
[0012] The zinc salt is at least one of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate; the molybdate is at least one of sodium molybdate, potassium molybdate and ammonium molybdate.
[0013] The pH value is adjusted to 3.0-6.0.
[0014] More preferably, the pH value is adjusted to 3.5-4.5.
[0015] The temperature of the hydrothermal reaction is 120-220° C. and the time is 24-120 hours.
[0016] More preferably, the temperature of the hydrothermal reaction is 150-180° C. and the time is 48-96 hours.
[0017] The above-mentioned octamolybdate metal organic complex is used as a heterogeneous oxidative desulfurization catalyst in oxidative desulfurization.
[0018] The above-mentioned oxidative desulfurization steps are: dissolving the octamolybdate metal organic complex, oxidant and sulfur-containing compound in a solvent, and performing oxidative desulfurization at 30-50° C. and normal pressure.
[0019] Furthermore, the above solvent is chloroform.
[0020] The beneficial effects produced by the present invention are:
[0021] (1) The present invention provides a novel oxidative desulfurization catalyst composed of 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid / Zn 2+ Octamybdate metal-organic complex Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O. The complex is assembled into a structurally stable single crystal under hydrothermal conditions through special organic ligands, metal cations and octamolybdate clusters. The catalyst exhibits excellent catalytic effect on the oxidative desulfurization of thioanisole (MBT), and a desulfurization rate of 99.9% can be achieved in 120 minutes under mild conditions.
[0022] (2) The present invention uses octamolybdate metal organic complex as a catalyst, which shows excellent recycling performance. After 5 cycles, the catalytic efficiency is still maintained at 98%, and the catalyst shows good stability. There is no obvious change in the infrared spectrum before and after catalysis, which proves that the catalyst structure is not damaged and has the potential for long-term use.
[0023] (3) The catalyst of the present invention is a heterogeneous catalyst (insoluble in the reaction solvent). After the reaction is completed, it can be recovered and reused by simple filtration.
[0024] (4) The catalytic reaction conditions of the present invention are mild, do not require high temperature and high pressure, and are easy to operate and safe and reliable.
[0025] (5) The preparation method of the catalyst of the present invention is simple, easy to realize large-scale production, and has high commercial development value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The octamolybdate metal organic complex Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O is the basic structural unit of crystal.
[0028] Figure 2 The relationship between MBT conversion rate and reaction time under different temperature conditions.
[0029] Figure 3 Mass spectra of MBT (a) and the product after 90 minutes of oxidation (b).
[0030] Figure 4 It is the number of cycles of the octamolybdate metal organic complex catalyst prepared by the present invention.
[0031] Figure 5 The infrared spectra of the prepared octamolybdate metal organic complex before and after catalysis. The top curve represents before catalysis, and the bottom one represents after 5 cycles of catalysis. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] An octamolybdate metal organic complex, the molecular formula of which is: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 organic ligand and twenty-four crystal water molecules; the unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0034] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps: dissolving zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate in distilled water, stirring at room temperature, and adjusting the pH value to acidic to obtain a suspension; subjecting the suspension to a hydrothermal reaction, and after the reaction is completed, naturally cooling to room temperature, washing, and drying to obtain regular colorless crystals, namely the octamolybdate metal organic complex.
[0035] The molar ratio of the zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate is (3.5-5.5):(1.2-2.5):1.
[0036] More preferably, the molar ratio of the zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate is (4.0-5.0):(1.5-2):1.
[0037] The zinc salt is at least one of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate; the molybdate is at least one of sodium molybdate, potassium molybdate and ammonium molybdate.
[0038] The pH value is adjusted to 3.0-6.0.
[0039] More preferably, the pH value is adjusted to 3.5-4.5.
[0040] The temperature of the hydrothermal reaction is 120-220° C. and the time is 24-120 hours.
[0041] More preferably, the temperature of the hydrothermal reaction is 150-180° C. and the time is 48-96 hours.
[0042] Example 1
[0043] The octamolybdate metal organic complex of this embodiment has the molecular formula: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 ligand and twenty-four crystal water molecules; its unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0044] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps:
[0045] Zinc sulfate heptahydrate (0.103 g, 0.359 mmol), 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid (0.034 g, 0.134 mmol), ammonium molybdate (NH4)6Mo7O 24 (0.101g, 0.0817mmol) was mixed, dissolved in distilled water (8mL), and stirred at room temperature for 0.5 hours. 1mol / L HCl and 2mol / L NaOH solution were added to adjust the pH value of the system to 3.4. The resulting suspension was poured into a 25mL polytetrafluoroethylene-lined autoclave, heated at 160°C for 120 hours, naturally cooled to room temperature, rinsed with distilled water and dried, and finally regular colorless crystals were obtained, which were octamolybdate organic complex crystal materials. The prepared crystals were rinsed with distilled water and dried to obtain pure octamolybdate metal organic complex crystals, and the yield was 65.0% calculated based on ammonium molybdate.
[0046] In order to determine the crystal structure of the prepared octamolybdate metal organic complex, crystal data were collected using a Bruker APEX-II single crystal X-ray diffractometer at 298K using Mo-Kα radiation. Subsequently, the crystal structure was analyzed using the SHELXTL-97 software package, and the least squares method (F2) was used for structural refinement. The results show that all non-hydrogen atoms in the complex exhibit anisotropic distribution. For hydrogen atoms on organic carbon atoms, their positions are fixed according to the calculation results; while hydrogen atoms on water molecules, protonated organic ligands, and polyoxyanions are directly included in the final chemical formula because they cannot be clearly identified from weak diffraction peaks. Based on the above analysis, the molecular formula of the crystalline material was determined to be Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O. The relevant crystallographic parameters and structure refinement details are listed in Table 1.
[0047] Table 1 Crystal data and structure refinement of prepared octamolybdate metal organic complexes
[0048]
[0049]
[0050] a R1=∑||F o |-|F c || / ∑|F|. b wR2=|∑w(|F o | 2 -|F c | 2 ) 2 / ∑|w(F) 2 | 1 / 2 .
[0051] By conducting X-ray single crystal diffraction tests on the prepared octamolybdate metal organic complex and analyzing the data using SHELXTL-97 software, it was confirmed that the complex belongs to the triclinic system and the space group is P-1. Figure 1 As shown, the crystal structure consists of four zinc (II) cations (Zn 2+ ), 1 [Mo8O 26 ] 4- Polymolybdate anion, 4 protonated C 12 It is composed of H8N5O2 organic ligand and 24 crystal water molecules.
[0052] Example 2
[0053] The octamolybdate metal organic complex of this embodiment has the molecular formula: Zn4(Mo8O26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 ligand and twenty-four crystal water molecules; its unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0054] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps:
[0055] Zinc nitrate heptahydrate (0.096 g, 0.324 mmol), 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid (0.042 g, 0.163 mmol), sodium molybdate dihydrate (0.020 g, 0.0817 mmol) were mixed, dissolved in distilled water (8 mL), and stirred at room temperature for 0.5 hours. 1 mol / L HCl and 2 mol / L NaOH solution were added to adjust the pH value of the system to 4.5. The resulting suspension was poured into a 25 mL polytetrafluoroethylene-lined autoclave, heated at 150° C. for 96 hours, cooled naturally to room temperature, rinsed with distilled water and dried, and finally regular colorless crystals were obtained, which were octamolybdate organic complex crystal materials. The prepared crystals were rinsed with distilled water and dried to obtain pure octamolybdate metal organic complex crystals, and the yield was 60.2% calculated based on sodium molybdate dihydrate.
[0056] Example 3
[0057] The octamolybdate metal organic complex of this embodiment has the molecular formula: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 ligand and twenty-four crystal water molecules; its unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0058] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps:
[0059] Zinc chloride (0.11 g, 0.818 mmol), 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid (0.064 g, 0.25 mmol), potassium molybdate (0.039 g, 0.163 mmol) were mixed, dissolved in distilled water (16 mL), and stirred at room temperature for 0.5 hours. 1 mol / L HCl and 2 mol / L NaOH solution were added to adjust the pH value of the system to 3.5. The resulting suspension was poured into a 25 mL polytetrafluoroethylene-lined autoclave, heated at 180°C for 48 hours, cooled naturally to room temperature, rinsed with distilled water and dried, and finally regular colorless crystals were obtained, which were octamolybdate organic complex crystal materials. The prepared crystals were rinsed with distilled water and dried to obtain pure octamolybdate metal organic complex crystals, and the yield was 58.7% calculated with potassium molybdate.
[0060] Example 4
[0061] The octamolybdate metal organic complex of this embodiment has the molecular formula: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 ligand and twenty-four crystal water molecules; its unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0062] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps:
[0063] Zinc acetate (0.135 g, 0.734 mmol), 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid (0.073 g, 0.285 mmol), ammonium molybdate (NH4)6Mo7O 24(0.202g, 0.163mmol) was mixed, dissolved in distilled water (16mL), and stirred at room temperature for 0.5 hours. 1mol / L HCl and 2mol / L NaOH solution were added to adjust the pH value of the system to 4.0. The resulting suspension was poured into a 25mL polytetrafluoroethylene-lined autoclave, heated at 175°C for 72 hours, naturally cooled to room temperature, rinsed with distilled water and dried, and finally regular colorless crystals were obtained, which were octamolybdate organic complex crystal materials. The prepared crystals were rinsed with distilled water and dried to obtain pure octamolybdate metal organic complex crystals, and the yield was 62.2% calculated based on ammonium molybdate.
[0064] Example 5
[0065] The octamolybdate metal organic complex of this embodiment has the molecular formula: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 ligand and twenty-four crystal water molecules; its unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0066] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps:
[0067] Zinc sulfate heptahydrate (0.229 g, 0.815 mmol), 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid (0.083 g, 0.326 mmol), ammonium molybdate (NH4)6Mo7O 24 (0.202g, 0.163mmol) was mixed, dissolved in distilled water (16mL), and stirred at room temperature for 0.5 hours. 1mol / L HCl and 2mol / L NaOH solution were added to adjust the pH value of the system to 4.0. The resulting suspension was poured into a 25mL polytetrafluoroethylene-lined autoclave, heated at 220°C for 24 hours, naturally cooled to room temperature, rinsed with distilled water and dried, and finally regular colorless crystals were obtained, which were octamolybdate organic complex crystal materials. The prepared crystals were rinsed with distilled water and dried to obtain pure octamolybdate metal organic complex crystals, and the yield was 51.7% calculated based on ammonium molybdate.
[0068] Example 6
[0069] The octamolybdate metal organic complex of this embodiment has the molecular formula: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P-1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 ligand and twenty-four crystal water molecules; its unit cell parameters are: α=84.837(5)°, β=75.296(5)°, γ=76.479(5)°, Z=2, F(000)=1380.
[0070] The preparation method of the above-mentioned octamolybdate metal organic complex comprises the following steps:
[0071] Zinc sulfate heptahydrate (0.184 g, 0.652 mmol), 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid (0.062 g, 0.244 mmol), ammonium molybdate (NH4)6Mo7O 24 (0.202g, 0.163mmol) was mixed, dissolved in distilled water (16mL), and stirred at room temperature for 0.5 hours. 1mol / L HCl and 2mol / L NaOH solution were added to adjust the pH value of the system to 4.0. The resulting suspension was poured into a 25mL polytetrafluoroethylene-lined autoclave, heated at 120°C for 120 hours, naturally cooled to room temperature, rinsed with distilled water and dried, and finally regular colorless crystals were obtained, which were octamolybdate organic complex crystal materials. The prepared crystals were rinsed with distilled water and dried to obtain pure octamolybdate metal organic complex crystals, and the yield was 45.0% calculated based on ammonium molybdate.
[0072] Application Examples
[0073] The oxidative desulfurization catalytic activity of the octamolybdate metal organic complex prepared by the present invention was studied, and the specific experimental process and results are as follows.
[0074] Thioanisole (MBT), a common sulfur-containing compound in fuel, was selected as a model substrate to study the activity of the prepared octamolybdate metal organic complex in the catalytic oxidation desulfurization process. The specific steps include adding 0.25 mmol of MBT and 1 mmol of tert-butyl hydroperoxide (TBHP) to 5 ml of chloroform solution, followed by adding 10 mg of the target catalyst (i.e. the prepared octamolybdate metal organic complex), and heating the mixed system to a specified catalytic temperature (30-50°C) at normal pressure for reaction. Samples were taken every 30 minutes, and the catalyst was separated from the reaction mixture by centrifugation. The MBT concentration in the oil phase was then detected by gas chromatography (GC), and the oxidation products of MBT were identified by gas chromatography-mass spectrometry (GC-MS).
[0075] The experimental results show that the prepared octamolybdate metal organic complex exhibits excellent catalytic performance during the oxidative desulfurization process of MBT. When the reaction temperature increases from 30 degrees Celsius to 40 degrees Celsius, the conversion rate of MBT increases. However, when the temperature continues to rise to 50 degrees Celsius, the conversion rate does not change significantly, thus determining 40 degrees Celsius as the optimal catalytic temperature. After the reaction lasts for 120 minutes, the conversion rate of MBT reaches a nearly complete level, as high as 99.9% ( Figure 2 In addition, the product after 90 minutes of reaction was analyzed (see Figure 3 ), GC-MS results showed that the product mainly contained two forms: sulfone and sulfoxide.
[0076] It is worth noting that the catalyst is insoluble in the solvent and can be effectively recovered and reused by a simple centrifugation operation. After five cycles of use, although the catalytic activity decreased slightly (see Figure 4 ), but still maintains a catalytic efficiency of up to 98.0%, showing good stability and reusability. Infrared spectroscopy analysis further confirmed that the structure of the catalyst did not change significantly before and after the reaction (such as Figure 5 As shown in Figure 2, it shows that its structural stability is good. In summary, the octamolybdate metal organic complex prepared in this study, as a heterogeneous catalyst, shows efficient catalytic performance in the application of fuel oxidation desulfurization.
[0077] The preparation method provided by the present invention is simple and easy, and high-quality single crystals can be obtained, and the crystal structure is stable. The recovery process of the catalyst after the reaction is completed is simple and fast, and only filtering is required. In addition, the preparation process of the catalyst is easy to scale up production and has high commercial potential. The prepared octamolybdate metal organic complex can not only provide an efficient catalytic means for fuel oxidation desulfurization, but also help to improve related environmental issues such as air quality. More importantly, by selecting different ligands and metal ions, more diverse POM-based organic complexes can be designed, providing a broad exploration space for finding more efficient fuel oxidation desulfurization catalysts.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An octamolybdate metal organic complex, characterized in that: The molecular formula of the octamolybdate metal organic complex is: Zn4(Mo8O 26 )(C 12 H8N5O2)4·24H2O; triclinic system, P -1 space group, the basic unit contains four Zn(II) cations, one [Mo8O 26 ] 4- Polyanion, four C 12 H8N5O2 organic ligand and twenty-four crystal water molecules; the unit cell parameters are: a =10.614(5) Å, b =13.348(5) Å, c =16.715(5) Å, α = 84.837(5)°, β = 75.296 (5)°, γ =76.479(5)°, V = 2225.9(15) Å 3 , Z = 2, F (000) = 1380.
2. The method for preparing the octamolybdate metal organic complex according to claim 1, characterized in that: The steps are as follows: zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate are dissolved in distilled water, stirred at room temperature, the pH value is adjusted to acidic, and then subjected to hydrothermal reaction to obtain.
3. The method for preparing the octamolybdate metal organic complex according to claim 2, characterized in that: The molar ratio of the zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate is (3.5-5.5): (1.2-2.5):
1.
4. The method for preparing the octamolybdate metal organic complex according to claim 3, characterized in that: The molar ratio of the zinc salt, 2,6-bis(1H-pyrazol-1-yl)isonicotinic acid and molybdate is (4.0-5.0): (1.5-2):
1.
5. The method for preparing the octamolybdate metal organic complex according to any one of claims 2 to 4, characterized in that: The zinc salt is at least one of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate; the molybdate is at least one of sodium molybdate, potassium molybdate and ammonium molybdate.
6. The method for preparing the octamolybdate metal organic complex according to claim 5, characterized in that: The pH value is adjusted to 3.0-6.
0.
7. The method for preparing the octamolybdate metal organic complex according to claim 6, characterized in that: The temperature of the hydrothermal reaction is 120-220° C. and the time is 24-120 hours.
8. The method for preparing the octamolybdate metal organic complex according to claim 7, characterized in that: The temperature of the hydrothermal reaction is 150-180° C. and the time is 48-96 hours.
9. Use of the octamolybdate metal organic complex according to claim 1 as a heterogeneous oxidative desulfurization catalyst in oxidative desulfurization.
10. The use according to claim 9, characterized in that: The oxidative desulfurization step is: dissolving the octamolybdate metal organic complex, the oxidant and the sulfur-containing compound in a solvent, and performing oxidative desulfurization at 30-50° C. and normal pressure.
Citation Information
Patent Citations
FCC (Fluid Catalytic Cracking) gasoline oxidation desulphurization method based on molybdenum polyoxometallate
CN103666536A
Zirconium-based molybdate oxidative desulfurization catalyst as well as preparation method and application thereof
CN116726993A
Cited By
Nickel-based metal organic framework and preparation method and detection application thereof
CN121045579A